Verification of a Reactor’s Digital Acoustic Model in the Startup and Nominal Operation Modes of NPPs Equipped with VVER Reactors - Proskuryakov, K. N.; Anikeev, A. V.; Afshar, E. (Thermal engineering, 2021)
— At present, the regulatory technical documents developed in the late 21st century that stipulate design solutions and operating regulations for nuclear power plants do not include provisions for predicting and preventing the occurrence of vibroacoustic resonances of structures involving acoustic standing waves (ASWs) in operational and emergency modes and also under the effect of seismic waves. This results in that the existing feedbacks between neutronic and thermophysical processes under the conditions of coolant density fluctuations caused by ASWs have not been given proper attention. A nuclear reactor digital acoustic model (NRDAC), using which it is possible to identify the sources of self-exciting ASWs and to predict their frequency, has been developed at the NRU MPEI Department of Nuclear Power Plants. The article presents a new method for identifying the ASW frequencies in the acoustic system comprising a pressurized water reactor (in its Russian version known as a VVER, meaning a water-cooled, water moderated power-generating reactor) with the cold and hot leg pipelines connected to it. The models and analysis methods have passed verification in the Novovoronezh NPP unit 3 equipped with a VVER-440 reactor. For measuring the autospectral power densities (ASPD) of pressure pulsations, the main equipment vibration monitoring system SÜS developed by Siemens was used. The predicted values of ASW frequencies are consistent with the signals measured by pressure pulsation sensors. It is shown that the ASW frequencies depend on the operation conditions and may coincide with the pressure fluctuation frequencies caused by the operation of reactor coolant pumps (RCPs) with vibration of fuel assemblies (FAs) and equipment of the NPP reactor coolant system. It is shown that, whatever the number of coolant circulation loops, the nuclear reactor acoustic properties are similar to the properties of a group of simultaneously used Helmholtz resonators. By using the verified procedure, it is possible to optimize the design and layout solutions by constructing equipment able to minimize undesirable cyclic loads. This possibility is the most important one from the viewpoint of ensuring long-term operation of small modular reactors in maneuverable modes. Small NPPs should be highly maneuverable to complement renewable energy sources. The majority of small modular reactors are designed for little-attended operation with long periods of time between refueling outages (2–10 years vs. 12–24 months in large power units) or with the fuel loaded for the entire life cycle. The requirements of ensuring long-term operation in maneuverable modes can be fulfilled subject to minimizing the dynamic loads applied to the reactor plant structures by preventing the occurrence of hydrodynamic instability and resonances of structural vibration with acoustic fluctuations of coolant.